الأوضاع الاجتماعية والسياسية في ليبيا ما بعد التدخل الدولي عام 2011م (Journal of Academic Research, 2025)
After the NATO-led military intervention in 2011, Libya entered a phase of deep political and social instability.The academic paper reviews the impact of this intervention on the country’s social fabric and political institutions.Politically, the fall of Muammar Gaddafi’s regime created a major institutional vacuum that the political forces were unable to fill in an organized manner. The subsequent period was marked by power struggles, the emergence of parallel governments, and repeated failures to establish a unified central authority. Regional and international interventions further complicated the situation, as various external actors supported rival factions within Libya, deepening internal divisions.Socially, the security vacuum led to increased tribal and regional conflicts, the widespread circulation of weapons, and the rise of armed groups operating outside the law. The quality of life for Libyan citizens deteriorated significantly, with basic services declining and rates of internal displacement and illegal migration rising.The paper also discusses the absence of a unifying national project and the failure of political elites to build strong state institutions, leaving the country in a state of "failed statehood" by many international indicators. It emphasizes that the solution cannot be purely military, but rather requires an inclusive national dialogue, supported by balanced and impartial regional and international efforts